Psychoeducation reduces anxiety and cortisol hormones in high-risk pregnant women - Sahupala, Sapiah; Suharsono, Suharsono; Wijayanti, Krisdiana (Universitas Muhammadiyah Purwokerto, 2025)
Background: High-risk pregnancy poses significant challenges to both maternal and fetal health, increasing the risk of complications, anxiety, and elevated cortisol levels. Anxiety in high-risk pregnancies has been widely studied, but most interventions focus on pharmacological treatments or psychological support without integrating physiological stress markers such as cortisol levels. Psychoeducation is a nonpharmacological intervention designed to enhance understanding, equip women with stress management skills, and promote confidence in facing pregnancy. However, limited studies have examined its direct impact on both anxiety and cortisol levels in high-risk pregnant women.Purpose: This study aims to evaluate the effectiveness of psychoeducation in reducing anxiety and cortisol levels among high-risk pregnant women.Methods: This study employed a pre-experimental one-group pretest-posttest design without a control group. The intervention consisted of four structured psychoeducation sessions, each lasting 120 minutes over two weeks. A total of 23 high-risk pregnant women participated in the study. Anxiety levels were measured using the DASS-21, and cortisol levels were assessed through saliva samples collected before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test.Results: The findings revealed a significant reduction in anxiety scores from 15.60 ± 2.99 to 8.52 ± 1.88 (p < 0.001) and cortisol levels from 15.72 ± 9.10 to 10.40 ± 6.97 (p < 0.001), indicating the effectiveness of psychoeducation in reducing both psychological and physiological stress in high-risk pregnancies.Conclusion: Psychoeducation, delivered through four sessions over two weeks, is effective in reducing anxiety and cortisol levels in high-risk pregnant women. This intervention should be integrated into prenatal care to support maternal well-being and stress management.